A comparative analysis of online learning versus face-to-face learning approach in problem based learning in dentistry. - Li, Guang; Alam, Beenish Fatima; Bashir, Raima; Tarhini, Ali; Nayab, Talha (Work, 2024)
BACKGROUND: Problem-based learning (PBL), a student-centered approach which has been implemented in many educational institutes worldwide. OBJECTIVES: This study aimed to evaluate and compare the proficiency of students in 5 key areas of PBL process and assess perceptions of students towards PBL learning using a self-explanatory questionnaire. METHOD: This cross-sectional study was conducted from March 2020 to September 2022 and evaluated perceptions of 1st year dental students of Batch 2021 (having Face-to-face PBL sessions) and batch 2020 (having online PBL sessions) using a questionnaire. Three similar PBL cases were used, which assessed PBL parameters that included attendance, group dynamics, knowledge, communication skills and preparation. Statistical analysis was performed for all the categorical and continuous variables. RESULTS: Majority of Distance Learning (DL) group (66.7%) concurred that PBL helped improve their communication skills, decision making power (66.7%), self-directed learning (80%) and promoted interaction with peers (66.7) and teachers (68.9%). The Face –to- Face (FF) group demonstrated better scores (7.7±2.42 & 7.55±2.55) with respect to their attendance and group dynamics (7.44±2.17 & 8.02±2.40) in PBL 1 & 3 as compared to DL group. Overall, better performance in all the 5 key areas of PBL was observed for the FF group versus the DL group. CONCLUSION: The Distance learning (DL) group displayed a positive attitude and perception towards PBL as a learning strategy whereas Face-to-face (FF) group showed greater performance and proficiency in the key PBL parameters scores.